2016
DOI: 10.3389/fpsyg.2016.00574
|View full text |Cite
|
Sign up to set email alerts
|

Screen Time on School Days and Risks for Psychiatric Symptoms and Self-Harm in Mainland Chinese Adolescents

Abstract: Objective: To investigate associations of television and of video game or non-educational computer use (VG/CU) exposure volumes in a typical school day with psychiatric symptoms and suicidal ideation/self-injurious behavior (self-harm), in mainland Chinese adolescents.Methods: Secondary school pupils (N = 13,659; mean age: 15.18 ± 1.89) from 10 urban areas sampled from different regions of mainland China were recruited. The subjects were divided into the following four screen exposure volume groups for televis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 46 publications
2
34
1
1
Order By: Relevance
“…Associations between changes in screen-time and psychological difficulties were inconclusive and television/DVD use was the only significant association found. Previous research examining the relationship between screen-time and psychological difficulties has also produced inconsistent findings in cross-sectional (Booker et al, 2015;Busch et al, 2013;Liu, Ming, Yi, Wang, & Yao, 2016) and longitudinal studies (Booker et al, 2015;Chen & Lu, 2009;Parkes et al, 2013)(O'Connor et al, 2016Parkes et al, 2013) in young people. It is possible the varying outcomes may be due to differences in the measurement of screentime (in addition to the combining of time engaged in television and DVD viewing) and or the duration of follow-up periods.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Associations between changes in screen-time and psychological difficulties were inconclusive and television/DVD use was the only significant association found. Previous research examining the relationship between screen-time and psychological difficulties has also produced inconsistent findings in cross-sectional (Booker et al, 2015;Busch et al, 2013;Liu, Ming, Yi, Wang, & Yao, 2016) and longitudinal studies (Booker et al, 2015;Chen & Lu, 2009;Parkes et al, 2013)(O'Connor et al, 2016Parkes et al, 2013) in young people. It is possible the varying outcomes may be due to differences in the measurement of screentime (in addition to the combining of time engaged in television and DVD viewing) and or the duration of follow-up periods.…”
Section: Discussionmentioning
confidence: 98%
“…Although such examinations were beyond the scope of this study, previous findings suggest that elevated levels of psychological distress can lead to changes in behavior in adolescence. Studies have shown that television use (especially if the content is violent) may increase conduct problems (Parkes et al, 2013) (Liu et al, 2016), and may predict aggression and attention problems (Strasburger, Jordan, & Donnerstein, 2010;Zimmerman & Christakis, 2007). The nature of screen viewing (how adolescents watch, what they watch, and with whom) may have also been important implications for their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, self-harm behaviours that are common in Chinese young people (Liu et al, 2016;Xin et al, 2016;Xin et al, 2017) significantly increased suicidal ideation and attempt for both TW and TM. While a previous study reported that TM appear more vulnerable to self-harm behaviors than TW (Peterson et al, 2017), the present study found that TW have significantly higher self-harm behavior than TM.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] A growing number of studies have found an association between high levels of internet use in young people and poor mental health, including depression, anxiety, attention deficit hyperactivity disorder, hostility/aggression, suicidal ideation, and self-harm. [3,[8][9][10][11][12][13][14][15][16] However, most existing research is based on cross-sectional data and so the temporal relationship between mental health problems and internet use is currently unclear. The lack of longitudinal studies assessing the consequences of screen-based activities was recently highlighted as a key limitation in the field.…”
Section: Introductionmentioning
confidence: 99%